2018
DOI: 10.1055/s-0038-1675803
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Sensitivity and Specificity of Ultrasound and Magnetic Resonance Imaging in the Diagnosis of Placenta Accreta

Abstract: Objective To assess and compare the sensitivity and specificity of ultrasonography and magnetic resonance imaging in the diagnosis of placenta accreta in patients with placenta previa. Methods This retrospective cohort study included 37 women, and was conducted between January 2013 and October 2015; 16 out of the 37 women suffered from placenta accreta. Histopathology was considered the gold standard for the diagnosis of placenta accreta; in its absence, a description of the intraoperative findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 24 publications
0
16
0
2
Order By: Relevance
“…As the cesarean section rate increases, the incidence of AIP has increased over the past 50 years (14). It is difficult for patients with AIP to strip the entire placenta after delivery, which leads to serious obstetric complications, such as hemorrhages, hysterectomy, and even maternal mortality (15,16). The molecular mechanisms of invasive placentation in AIP are poorly understood; it might be a combination of primary absence of the decidua or basal plate, abnormal maternal vascular remodelling, and excessive EVT invasion (17) In summary, PE and AIP are consequences of two opposing trophoblast invasion disorders.…”
Section: Introductionmentioning
confidence: 99%
“…As the cesarean section rate increases, the incidence of AIP has increased over the past 50 years (14). It is difficult for patients with AIP to strip the entire placenta after delivery, which leads to serious obstetric complications, such as hemorrhages, hysterectomy, and even maternal mortality (15,16). The molecular mechanisms of invasive placentation in AIP are poorly understood; it might be a combination of primary absence of the decidua or basal plate, abnormal maternal vascular remodelling, and excessive EVT invasion (17) In summary, PE and AIP are consequences of two opposing trophoblast invasion disorders.…”
Section: Introductionmentioning
confidence: 99%
“…For patients with PA, dissection of the entire placenta during delivery is difficult, which may lead to intrapartum and postpartum hemorrhage. The average hemorrhage size is large, and it is the main cause of perinatal emergency hysterectomy (4). The maternal mortality rate associated with PA is a serious obstetric complication (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Lopes et al, 19 reported that between the 37-cases (100%) who experienced the US, the PA-prevalence was 20 (54.2%) (95% confidence interval [95%CI]: 40.8-67.3).…”
Section: Discussionmentioning
confidence: 99%